On Pseudo Random Bit Generators via Two-Dimensional Hybrid Cellular Automata - Temiz, F.; Siap, I.; Akin, H. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
In this work, we study the structure of two-dimensional linear hybrid cellular automata with respect to adiabatic boundary condition. Further, we check the performance of hybrid cellular automata constructed through the members of this family in generating pseudo random bits.
Keywords: Physics